2013
DOI: 10.1371/journal.pone.0068943
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Egr-1 in Human Lung Epithelial Cells Exposed to Silica through MAPKs Signaling Pathways

Abstract: The alveolar type II epithelial cell, regarded historically as a key target cell in initial injury by silica, now appears to be important in both defense from lung damage as well as elaboration of chemokines and cytokines. The molecular basis for silica-induced epithelial cell injury is poorly understood. In this study we explored the activation of nuclear factor Egr-1 and related signal pathway. Human II alveolar epithelial line A549 cells were exposed to silica for indicated time to assay the expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…A role of ERK1/2 pathway in the upregulation of Egr‐1 expression by Apelin‐13, a ligand for G protein‐coupled receptor, as well as by TNF‐α, has also been demonstrated in VSMC [Goetze et al, ; Liu et al, ]. An involvement of ERK/JNK‐dependent mechanism in mediating Egr‐1 expression in non‐vascular cells in response to epidermal growth factor (EGF) [Gregg and Fraizer, ] and silica dust has also been reported [Chu et al, ]. These findings underscore the importance of MAPK pathways in transducing the signals of various stimuli leading to the enhanced expression of Egr‐1.…”
Section: Discussionmentioning
confidence: 86%
“…A role of ERK1/2 pathway in the upregulation of Egr‐1 expression by Apelin‐13, a ligand for G protein‐coupled receptor, as well as by TNF‐α, has also been demonstrated in VSMC [Goetze et al, ; Liu et al, ]. An involvement of ERK/JNK‐dependent mechanism in mediating Egr‐1 expression in non‐vascular cells in response to epidermal growth factor (EGF) [Gregg and Fraizer, ] and silica dust has also been reported [Chu et al, ]. These findings underscore the importance of MAPK pathways in transducing the signals of various stimuli leading to the enhanced expression of Egr‐1.…”
Section: Discussionmentioning
confidence: 86%
“…Although there are sparse data describing the cellular localization of Egr‐1 protein, a cytoplasmic activity of Egr‐1 is consistent with a role in transcriptional regulation through binding of co‐factors . Recent study has shown that Egr‐1 expression was increased and partly located in cytoplasm after a 30‐minute treatment with silica in human alveolar epithelial A549 cells . Nevertheless, further studies are needed to elucidate the role(s) of cytoplasmic Egr‐1 expression in the pathogenesis of OSF.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent study has shown that Egr-1 expression was increased and partly located in cytoplasm after a 30-minute treatment with silica in human alveolar epithelial A549 cells. 18 Nevertheless, further studies are needed to elucidate the role(s) of cytoplasmic Egr-1 expression in the pathogenesis of OSF.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies have shown that silica exposure causes lung inflammation, granuloma formation and emphysema (Lacher et al, 2010;Hnizdo and Vallyathan, 2003;Langley et al, 2010). Prior studies have demonstrated that lung epithelial cells are the primary targets of occupational exposure to silica and showed direct evidence of severe degeneration and damage following silica exposure (Chu et al, 2013;Kaewamatawong et al, 2005). Transmission electron microscopic studies suggest internalization of silica particles by these cells (McCracken et al, 2013).…”
Section: Discussionmentioning
confidence: 99%